1979
DOI: 10.1177/002221947901200213
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Training Interventions in Children: Review of a New Approach

Abstract: This paper reviews cognitive training studies with children showing behavioral, attentional, or cognitive problems. Various cognitive procedures have been employed, including self-instructional, problem solving, and component attentional skills training. The most consistently sensitive index of training effectiveness has been improved performance on the Matching Familiar Figures Test, a measure of cognitive impulsivity. Reports of improved reading performance suggest that cognitive training may enhance academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1

Year Published

1981
1981
1990
1990

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 37 publications
0
19
1
Order By: Relevance
“…Although CBM regimens vary, several typical components have been identified (Abikoff, 1979;Lloyd, 1980). Students learn to control their own behavior through processes such as self-instruction, self-monitoring, self-assessment, and self-reinforcement.…”
Section: Components Procedures and Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although CBM regimens vary, several typical components have been identified (Abikoff, 1979;Lloyd, 1980). Students learn to control their own behavior through processes such as self-instruction, self-monitoring, self-assessment, and self-reinforcement.…”
Section: Components Procedures and Applicationsmentioning
confidence: 99%
“…Denney & Turner, 1979;Keogh & Glover, 1980;Meichenbaum & J. Goodman, 1971;O'Leary, 1980), but further study of the relative effects of singular or combined components is needed. Recent reviews of research in this area have indicated that programs using abbreviated steps or differing components can significantly affect behavior (Abikoff, 1979;Finch & Spirito, 1980;Meichenbaum, 1979a).…”
Section: Components Procedures and Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the child fades out verbalized selfinstruction and then uses internalized speech to direct task performance. Abikoff ( 1979) evaluated 13 studies that used cognitive training to decrease impulsivity and hyperactivity and increase attending, and found the success of such strategies equivocal. The major difficulty appeared to lie not with the strategy itself but in the assumption that all impulsive or attentional behaviors belong to one response class (e.g., assuming impulsive task approach is similar to impulsive, inappropriate class behavior).…”
Section: Attentionmentioning
confidence: 99%